La restauration du crocodile historique du Muséum des Sciences naturelles d’Angers - Michel Beucher; Miguel Prôa (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Present throughout the History of Europe, crocodile taxidermy preparations conveyed a powerful symbolism until the 18th century. Due to their historical value, the conservation of such specimens requires special care and their restoration remains a delicate undertaking. The objective of this article is to highlight the exceptional restoration of a historical crocodile specimen belonging to the Museum Natural Sciences of Angers. We will discuss the elements of a possible ancient intervention on the specimen, such as a wooden internal architecture, the presence of sealant to fill gaps in the skin, leather parts inside the mouth or the use of printed book pages to fill in holes.